Reformation of students` educational achievements monitoring process in maritime educational institutions in 1990-1999 years of the XX century - Iryna Kutsenko (Kazimierz Wielki University, 2021)
The article highlights the historical improving of students` educational achievements monitoring process in maritime educational institutions in 1990-1999 of the XX century. Orders, reports, meetings of methodological associations and pedagogical meetings and other documents, the content of which is related to the educational activities of maritime educational institutions in general and monitoring, are analyzed. There was an urgent need for state monitoring of the education quality. Reforming the education ofUkraineand monitoring the academic achievements of students in maritime institutions in practice was associated with the emergence of testing and rating system.